Run, book one - Lewis, John 1940-2020; Aydin, Andrew 1983- (Abrams ComicArts, 2021)
"From the #1 New York Times bestselling, graphic novel series March comes the continuation of the life story of John Lewis and the struggles seen across the United States after the Civil Rights Movement. For John Lewis, the Civil Rights Movement as he knew it ended with the signing of the Voting Rights Act in 1965, but his struggle in the following years echo many of the same questions of civil rights and equality that are being asked today. The movement secured the right to sit at a lunch counter, but what about the right to earn a dollar to pay for your meal? Ousted from the Student Nonviolent Coordinating Committee due to internal disorder, Lewis went on to work on Robert F. Kennedy's campaign, to be shocked by the events of 1968. Struggling with the larger question of how to rebuild the movement, Lewis had an idea: someone should run for the 5th Congressional district seat in Georgia. Starting with the tragic death of Martin Luther King Jr., Run tells the story of how John Lewis entered politics, working within the community, and organizing a campaign that has taken him to one of the most important seats in Congress"...